The research of the cognitive component of value orientations of volunteering students - Podolianchuk , Diana (Psychological Prospects Journal, 2021)
Purpose. The article is devoted to the study of value orientations of students of the pedagogical university. The purpose of the article is to present the results of an empirical study of the features of the cognitive component of value orientations of students of the pedagogical university who participate in the volunteer movement.Methods. The study of theoretical aspects of the problem was carried out using general scientific methods (analysis, synthesis, generalization). The empirical study of students' value orientations was carried out using the method of studying the individual values of Schwartz, adapted by V. M. Karandashev. The obtained results were processed using the methods of mathematical statistics (Fisher's test, Student's test).Results. The analysis of theoretical sources allowed to state the importance of value orientations as personal factors of students' volunteer activity. At the same time, an important role in the structure of value orientations belongs to the cognitive component, which reflects the normative ideals of students, their values ("values-knowledge"), which to some extent affect the personality. As a result of the research, the absolute indicators of average values of different types of normative values and their rank for student-volunteers and students who are not engaged in volunteer activities are determined. Comparative analysis and the application of Fisher's and Student's criteria made it possible to identify differences in the attitudes of both groups of students to different types of values.Conclusions. The conducted study showed that there are no statistically significant differences concerning most types of normative values (security, conformity, hedonism, universalism, power, and traditions) between volunteering students and those who do not participate in volunteering at all. The values of benevolence and security are most important to all students. The main groups of values, the attitude to which distinguishes volunteering students from those who do not volunteer, are achievement and benevolence. With other groups of values (independence, stimulation) there are also some differences between students of the studied groups. However, with a significant difference in absolute averages, these differences do not reach the level of statistical significance. It is also worth noting the sufficient level of awareness of modern students with different types of normative values.
Keywords: values, normative values, value orientations, volunteer, volunteer activity, student, Schwartz’s method.